Images, perception, and relationships of the elderly with their grandchildren in selected rural and urban areas in Negros. - Monserate, Jevy Joy T.
The study was conducted to find what are the images of the grandchildren on the elderly in the rural and urban areas, what are their perceptions about their elderly, and their relationship with their elderly. Fifty (50) granchildren from Brgy. Taculing in Bacolod City and Brgy. Mabini in the Municipality of Valladolid ages 15-35 years old and with at least one living grandparent participated in the study. The instrument used in measuring the variables was the "Varying Images, Perception, and the Relationships of the Elderly" questionnaire by the University of Santo Tomas Social Research Center (1989). Results showed that respondents indicated negative images about being old such as being weak or sickly and forgetful or senile without much difference in terms of residence. Generally, urban respondents perceived their grandparents having more positive attributes such as being friendly, sociable, kind, and contented than their rural counterpart. In terms of their relationship, compared with the urban respondents, rural respondents appeared to have more problems encountered by way of how the grandparents treated the grandchildren and some grandparents were considered to be a problem by the grandchildren who take care of them.